Securing food, building livelihoods? A 15-year appraisal of Ethiopia's Productive Safety Net Programme - Hoddinott, John F.; Berhane, Guush; Gilligan, Daniel O.; Hirvonen, Kalle; Kumar, Neha; Lind, Jeremy; Sabates-Wheeler, Rachel; Taffesse, Alemayehu Seyoum (United Nations University, 2024)
-We assess the impact of a large-scale social protection intervention, Ethiopia’s Productive Safety Net Programme (PSNP), over a 15-year period. -We find that the PSNP had a positive impact on food security but inconsistent impacts on assets. There were positive impacts on fertilizer use, investments in terracing, and cereal yields but only when the program was twinned with complementary programming. -The PSNP enabled households to be more resilient to covariate shocks. There were no adverse incentive effects on labour supply or fertility. There is some evidence that it improved schooling outcomes and reduced child labour but not child nutrition outcomes. -Payment levels, uncertainty about when payments would take place, and processes associated with making payments all played a role in generating these mixed impacts. -These also illustrate that while complementary programming can enhance the impact of transfers, adding complementary programming at scale is challenging when resources are limited.